Associations between perceived social support, posttraumatic stress disorder (PTSD) and complex PTSD (CPTSD): implications for treatment. Issue 1 (1st January 2019) - Simon, Natalie; Roberts, Neil P.; Lewis, Catrin E.; van Gelderen, Marieke J.; Bisson, Jonathan I.
ABSTRACT: Background : Perceived social support (PSS) is one of the most important risk factors for the onset and maintenance of posttraumatic stress disorder (PTSD) symptoms, however the relationship between PSS and Complex PTSD (CPTSD) is unknown. The evidence-base for CPTSD treatment is currently lacking, though increasingly important given the recent publication of the ICD-11, which now allows for a formal diagnosis of CPTSD. Objective : This research aims to develop understanding of the relationship between PSS and CPTSD with a view to informing the development of new and existing treatments. Method : A cross-sectional study was undertaken with 246 individuals recruited to the National Centre for Mental Health (NCMH) cohort. Measures of PSS and PTSD/CPTSD were undertaken with this clinical sample and linear and logistic regression were conducted to assess for associations between PSS and the PTSD symptom clusters of DSM-5 and ICD-11, and to explore the predictive utility of any PSS association on the likelihood of a CPTSD presentation. Results : It was found that individuals with a presentation of CPTSD tend to exhibit lower levels of PSS, compared with individuals not presenting with CPTSD, and lower PSS had a statistically significant unique association with the likelihood of presenting with CPTSD. Conclusions : Intervention aiming to improve PSS could be particularly helpful for some individuals with CPTSD, especially those with disturbances in relationships, and there is opportunity to develop skills training within a phase-based approach to treatment that targets factors related to PSS.